Konstruksi Makna Self Acceptance Dalam Album Mono Karya Boygroup BTS Pada Penggemar ARMY Kota Manado - Adjidji, Suci Alawiyah; Tangkudung, Joanne Pingkan M.; Hera, Leviane Jackelin (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Social life in the era of globalization is increasingly becoming complex and sometimes imposes certain standards and and ultimately causes a lack of self-acceptance within a person. Self-acceptance is the ability of someone to make peace with themselves and accept all their strengths and weaknesses. BTS, a boy group from South Korea with global popularity, is spreading awareness about the importance of self-acceptance for their fans ARMY through an album titled "mono". This study aims to find out the experiences of BTS ARMY and how they construct the meaning of self-acceptance contained in the "mono" album. This study uses qualitative methods with Alfred Schutz's phenomenological theory to analyze the experiences and meanings of ARMY fans. The results of this study show that ARMY fans gain negative self-acceptance experiences and positive self-acceptance experiences from their experiences of self-acceptance in their daily lives. The meaning of self-acceptance in the album "mono" by boy group BTS which was constructed by Manado City ARMY fans is: (1) Appreciating Themselves and (2) To Get Happiness in Life. Kehidupan sosial yang semakin kompleks di era globalisasi terkadang memaksakan standar dan harapan tertentu kepada seseorang dan akhirnya menyebabkan kurangnya rasa penerimaan diri (self acceptance) dalam diri seseorang. Penerimaan diri (self acceptance) merupakan kemampuan seseorang untuk berdamai dengan diri sendiri serta menerima segala kelebihan dan kekurangan dirinya. BTS, sebuah boygroup asal Korea Selatan dengan kepopulerannya secara global, turut menyebarkan kesadaran mengenai pentingnya self acceptance untuk penggemar mereka ARMY melalui album berjudul “mono”. Tujuan penelitian ini adalah untuk mengetahui pengalaman penggemar ARMY dan bagaimana penggemar ARMY mengkonstruksi makna self acceptance yang terdapat dalam album “mono”. Penelitian ini menggunakan metode kualitatif dengan teori fenomenologi Alfred Schutz untuk menganalisa pengalaman dan pemaknaan penggemar ARMY. Hasil dari penelitian ini menunjukkan bahwa penggemar ARMY memperoleh pengalaman penerimaan diri negatif dan pengalaman penerimaan diri positif dari pengalaman mereka terhadap self acceptance dalam kehidupan mereka sehari-hari. Makna self acceptance dalam album “mono” karya boygroup BTS yang dikonstruksi penggemar ARMY Kota Manado yaitu: (1) Mengapresiasi Diri Sendiri, dan (2) Mendapatkan Kebahagiaan Dalam Hidup.